The 7SK snRNP associates with the little elongation complex to promote snRNA gene expression. - Egloff, S; Vitali, P; Tellier, M; Raffel, R; Murphy, S; Kiss, T (EMBO Press, 2017)
The 7SK small nuclear RNP (snRNP), composed of the 7SK small nuclear RNA (snRNA), MePCE, and Larp7, regulates the mRNA elongation capacity of RNA polymerase II (RNAPII) through controlling the nuclear activity of positive transcription elongation factor b (P-TEFb). Here, we demonstrate that the human 7SK snRNP also functions as a canonical transcription factor that, in collaboration with the little elongation complex (LEC) comprising ELL, Ice1, Ice2, and ZC3H8, promotes transcription of RNAPII-specific spliceosomal snRNA and small nucleolar RNA (snoRNA) genes. The 7SK snRNA specifically associates with a fraction of RNAPII hyperphosphorylated at Ser5 and Ser7, which is a hallmark of RNAPII engaged in snRNA synthesis. Chromatin immunoprecipitation (ChIP) and chromatin isolation by RNA purification (ChIRP) experiments revealed enrichments for all components of the 7SK snRNP on RNAPII-specific sn/snoRNA genes. Depletion of 7SK snRNA or Larp7 disrupts LEC integrity, inhibits RNAPII recruitment to RNAPII-specific sn/snoRNA genes, and reduces nascent snRNA and snoRNA synthesis. Thus, through controlling both mRNA elongation and sn/snoRNA synthesis, the 7SK snRNP is a key regulator of nuclear RNA production by RNAPII.